2008
DOI: 10.1007/s00441-008-0577-9
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of rat ventral prostate after castration involves heparanase-1

Abstract: Androgen deprivation causes the rat ventral prostate to reduce to 10% of its original size by 21 days after castration. The regressive changes result from the loss of epithelial cells by apoptosis and marked reorganization of the stroma. We have investigated whether these changes are accompanied by variations in heparanase expression. The ventral prostate of castrated rats was collected and processed for the quantification of heparan sulfate (HS), for the measurement of heparanase expression and its localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 27 publications
1
28
0
6
Order By: Relevance
“…As we have focused our study on the epithelium, the epithelial regressive changes observed (i.e., a decrease in the amount of epithelial cells) could be either due to a low rate of cell proliferation, an increase of the apoptosis, or both. The androgenic blockade causes a decrease in the global size of the peripubertal ventral prostate, according to that described by other authors, which concern the regressive changes shown in the prostate after androgenic deprivation in both adult and prepubertal rats (Vilamaior et al, 2006;Pereira et al, 2006;Augusto et al, 2008). Controversy exists regarding the influence of PL on the prostate of pharmacologically castrated rats (either immature or mature).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…As we have focused our study on the epithelium, the epithelial regressive changes observed (i.e., a decrease in the amount of epithelial cells) could be either due to a low rate of cell proliferation, an increase of the apoptosis, or both. The androgenic blockade causes a decrease in the global size of the peripubertal ventral prostate, according to that described by other authors, which concern the regressive changes shown in the prostate after androgenic deprivation in both adult and prepubertal rats (Vilamaior et al, 2006;Pereira et al, 2006;Augusto et al, 2008). Controversy exists regarding the influence of PL on the prostate of pharmacologically castrated rats (either immature or mature).…”
Section: Discussionmentioning
confidence: 84%
“…Although the rat prostate is an androgen-dependent organ, several studies indicate that it is androgen-sensitive, but does not require a chronic androgenic stimulus (Donjacour and Cunha, 1988). This androgen-dependence was demonstrated by the dramatic changes observed in rat prostate after surgical or pharmacological castration: androgenic deprivation causes regressive alterations due to the decrease of epithelial cells by apoptosis and to stromal reorganization (Potter et al, 2006;Augusto et al, 2008). In this sense, cyproterone acetate (CA), currently employed in antiandrogenic therapy for prostate cancer, is a potent and specific antagonist of steroid androgens in competition with dihydrotestosterone in the binding of androgen receptors (AR).…”
mentioning
confidence: 99%
“…2). This *50 kDa band correspond to the active form of HPSE-1 previously identified in the VP (Augusto et al 2008), and established the specificity of the antibody. Densitometric analysis of the bands, considering total actin as internal control revealed a 33% reduction in HPSE-1 content in the VP of estogenized animals.…”
Section: Resultsmentioning
confidence: 96%
“…Its activity was associated with cellcell and cell-ECM interactions, and was first described in tumor progression. It is well known that tumor prostate cells and also normal rat prostate cells express HPSE-1 (Kosir et al 1997;Augusto et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation